Fenotipagem de alto desempenho para pigmentos foliares em genótipos de alface verde - Duarte, Jéssyca Gonçalves (2021)
Lettuce cultivation has great socioeconomic importance in Brazil. As it is a vegetable present in the diet, lettuce breeders have sought to develop new biofortified cultivars. One of the obstacles has been the high cost of the analyzes carried out in the laboratory, combined with the demand for time in the field. The objective of this study was the validation of imaging techniques using an Unmanned Aerial Vehicle (UAV) for the selection of biofortified lettuce genotypes. The experiment was carried out in a greenhouse at the Federal University of Uberlândia without a randomized block design with 25 treatments and 4 replications. Four different vegetation indices (NDVI, CVI, GNDVI and CIG), leaf pigments (chlorophyll a, b and total, carotenoid, lutein) and the Soil Plant Analysis Development (SPAD) index were evaluated. Data were prepared by analysis of variance using the F test (p ≤ 0.05). Means were compared using the Scott-Knott test (p ≤ 0.05). The genetic dissimilarity was represented by a dendrogram described by the hierarchical method of Unweighted Pairs-Groups Method Using the Arithmetic Mean (UPGMA). A correlation between vegetation indices versus pigments was evaluated, and the different vegetation indices were able to indirectly measure leaf pigments in green-faced germplasm. The correlation between pigments, SPAD and NDVI index was confirmed. Lettuce germplasm with wide genetic variability may interfere with correlation values. Therefore, it is suggested that the different vegetation indices be analyzed individually for each genotype (per se).